Rastlinstvo in deloma rastje soteske Zale v zgornjem porečju Iške - Accetto, Marko (Zbornik gozdarstva in lesarstva, 2013)
Between 2005 and 2009 and especially in 2011 and 2012, we studied the flora and partly vegetation of the Zala Gorge (Dinaric phytogeographical region, research area 403.2 ha). We divided the area under discussion into 40 units. We recorded all present taxa in each of them during different seasons. The results of floristic observations are shown by units, altitudinal belts and stream banks. We tested both floristic and ecological similarities between units by mathematicalstatistical methods. After analysis of groups of phytosociologic, chorological and plant life forms, we tested their density statistically by altitudinal belts and stream banks. Altogether, we recorded 503 taxa, 122 (24 %) of which were observed for the first time. The particularities of the Zala Gorge's flora are three endemic taxa, the long-known endemic species Primula carniolica now listed in Annexes II and IV of the EU FFH Directive, rare endemic species Scabiosa hladnikiana and recently described stenoendemic taxon Heliosperma veselskyi subsp. iskense, numerous Alpine, southeast-Alpine-Illyrian, southeast-European and other protected and threatened taxa. The results of the floristic and partly vegetation investigations show unique floristic and vegetational diversity of the Zala Gorge, which is distinguished floristically and ecologically from the recently described Iški vintgar. The new described syntaxa are: Scabioso hladnikianae Caricetum sempervirentis, Valeriano saxatilis-Molinietum arundinaceae, Omphalodo-Fagetum aretosum maculatae, -luzuletosum luzuloidis, -mercurialetosum perennis with variants Festuca altissima, Hordelymus europaeus and Ctenidium molluscum, -homogynetosum sylvestris, -cardaminetosum pentaphylli with variants Fraxinus excelsior and Geranium nodosum, Ostryo carpinifoliae-Piceetum and Bazzanio-Abietetum huperzietosum selaginis.
Keywords: dinarsko fitogeografsko območje; ecology; ekologija; flora; reka Iška; Slovenia; Slovenija; soteska Zala; vegetacija